2005
DOI: 10.1063/1.1869541
|View full text |Cite
|
Sign up to set email alerts
|

In situ resistance measurement of the p-type contact in InP–InGaAsP coolerless ridge waveguide lasers

Abstract: Scanning voltage microscopy (SVM) is employed to measure the voltage division—and resulting contact resistance and power loss—at the p-In0.53Ga0.47As–p-InP heterojunction in a working InP–InGaAsP laser diode. This heterojunction is observed to dissipate ∼35% of the total power applied to the laser over the operating bias range. This in situ experimental study of the parasitic voltage division (and resulting power loss and series contact resistance) highlights the need for a good p-type contact strategy. SVM te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In our device, the upper 200 nm of the ridge is composed of a highly doped p+ InGaAs region to achieve ohmic contacts and minimize contact resistance. However, by scanning the voltage along the laser facet Kuntze et al have shown that while minimizing metal-semiconductor contact resistance this approach generates a large voltage drop and thus heat generation at the p+ -p interface [19]. This can be characterized by another contact resistance, which they found to be 6x10 -9 Ωm 2 .…”
Section: Device Structurementioning
confidence: 99%
“…In our device, the upper 200 nm of the ridge is composed of a highly doped p+ InGaAs region to achieve ohmic contacts and minimize contact resistance. However, by scanning the voltage along the laser facet Kuntze et al have shown that while minimizing metal-semiconductor contact resistance this approach generates a large voltage drop and thus heat generation at the p+ -p interface [19]. This can be characterized by another contact resistance, which they found to be 6x10 -9 Ωm 2 .…”
Section: Device Structurementioning
confidence: 99%
“…Recently Atomic Force Microscopy (AFM) equipped with sensitive capacitance [1,2], conductivity [3] or resistance [4] sensors was used to measure electrical parameters of semiconductors. The most straightforward is KPFM method, which directly measures electrostatic forces.…”
Section: Introductionmentioning
confidence: 99%